Implementation of Islamic Education: Recitation of Asmaul Husna and Smiling-Greeting to Strengthen Children's Character - Subaidi; Imron Fauzi; Nunu Mahnun (Journal of Islamic Education Research, 2024)
This research aims to explain how to strengthen students' characters through the implementation of Islamic Education in the form of Asmaul Husna chanting and smiling-handshaking at Kemala Bhayangkari 44 Kindergarten in Kudus. The research approach is qualitative, conducted at the school location. The research data consists of primary and secondary data. Data collection techniques include observation, interviews, and documentation, while data analysis involves steps such as data reduction, data presentation, conclusion-making, and verification. The research results are as follows: first, strengthening students' religious characters, through the habituation of Asmaul Husna chanting and smiling-handshaking, is capable of educating students' characters in increasing faith and devotion to Allah, as well as developing personality and integrity towards fellow humans and other creatures; second, reinforcing discipline characters, one of its manifestations is that students are active in implementing the habituation of Asmaul Husna chanting and smiling-handshaking. This discipline character is an attitude and behavior born as a result of training or habituation to obey rules, laws, or orders; third, strengthening honest characters. When participating in Asmaul Husna chanting and smiling-handshaking, students actively and honestly follow the guidance of their respective teachers; fourth, strengthening peaceful characters. The school strives as much as possible for students to grow and develop their characters, including a peaceful and loving character initiated by the habituation of Asmaul Husna chanting and handshaking every day at the school.